Chemical variability in volatile oils of Bentong ginger: A chemometric study / Farah Syuhaidah Ahmad Jahiddin - Farah Syuhaidah , Ahmad Jahiddin (2020)
The volatile oil of ginger (Zingiber officinale) possesses various pharmacological properties corresponding to its chemical compositions, which in turn, depends on its source material and preparation method. In this study, preliminary experiments were carried out to investigate the variations in volatile oil of ginger prepared based on different method (dry/fresh samples), extraction duration and size reduction process (grate/slice samples). The ginger volatile oil yield can be quantitatively improved by using a fresh sample with grated form and a longer extraction cycle. Gas Chromatography-Mass Spectrometry (GC-MS) was conducted and the chromatogram profile was subjected to Principal Component Analysis (PCA). Results show that extract of fresh samples was predominated by the presence of monoterpenes while sesquiterpenes were more profound in the grated samples; meanwhile, the extraction duration demonstrated a direct and inverse relationship on monoterpenes and sesquiterpenes. As the optimum extraction procedure has been determined, the variability in the volatile components was further explored using pattern recognition tools. The results revealed a tendency for the volatile oil components to cluster, probably due to the geographic origin of the ginger material, therefore highlighting that the terpene components in Bentong ginger could be used to differentiate it from other commercial gingers. The overall findings demonstrate that different sample preparation methods and geographical origin will affect the quantity and/or quality of ginger extract obtained.